CM‐AVM syndrome – A prospective observational study of unrelated paediatric cases. (25th June 2021) - Haefliger, Stefanie; Adams, Susan; Nandakumar, Archana; Nguyen, Linh; Wargon, Orli
Abstract: Objective: The main objective of this study is to describe the clinical spectrum of CM‐AVM syndrome as well as radiological and genetic findings. Methods: This is a single‐centre prospective observational study performed at Sydney Children's Hospital. Patients under the age of 18 years that presented to our paediatric dermatology clinic or vascular birthmark clinic between January 2015 and September 2020 with one or more geometric shaped pink/ red/ brown macule with a peripheral pallor characteristic of a high‐flow vascular stain were included. Children subsequently diagnosed with other diagnosis or family members with CM‐AVM syndrome were excluded. Results: Sixty children were included, with two subsequently excluded. A third of patients ( n = 22, 38%) presented with a single characteristic HFVS, whereas the remaining two thirds ( n = 36; 62%) had multiple HFVS. In children with multiple HFVS, one notably larger HFVS was detected in the majority of children ( n = 32, 88%). In 33 patients, a brain and spine MRI was performed, which detected a spine AVM in one symptomatic patient with sensorimotor deficits. No cerebral AVM or AVF was picked up in the cohort. A RASA 1 result was available for evaluation in 24, of which 16 (67%) were positive. An EPHB4 result was available in eight, two (25%) of which were positive. Conclusions: One large HFVS often accompanied by multiple small HFVS can be seen in most patients. Despite of the lack of genetic confirmation of diagnosis in single lesions, this phenotype might be of interest and warrants further investigation.